Maternal and fetal/neonatal outcomes of pregnancies complicated by pulmonary hypertension: a retrospective study of 154 patients (Clinics, 2023)
Objectives: To determine the main clinical and demographic outcomes related to Pulmonary Hypertension (PH) and adverse obstetric and fetal/neonatal outcomes.Methods: This study retrospectively analyzed the medical record data of 154 patients with PH who were admitted to the Third Affiliated Hospital of Guangzhou Medical University between January 2011 and December 2020.Results: According to the severity of elevated Pulmonary Artery Systolic Pressure (PASP), 82 women (53.2%) were included in the mild PH group, 34 (22.1%) were included in the moderate PH group, and 38 (24.7%) were included in the severe PH group. There were significant differences in the incidence of heart failure, premature delivery, Very-Low-Birth-Weight (VLBW) infants, and Small-for-Gestational-Age (SGA) infants among the three PH groups (p < 0.05). Five (3.2%) women died within 7-days after delivery, 7 (4.5%) fetuses died in utero, and 3 (1.9%) neonates died. The authors found that PASP was an independent risk factor for maternal mortality. After adjustment for age, gestational weeks, systolic blood pressure, Body Mass Index (BMI), mode of delivery, and anesthesia, the risk of maternal mortality in the severe PH group was 20.21 times higher than that in the mild-moderate PH group (OR = 21.21 [95% CI 1.7∼264.17]), p < 0.05. All 131 (85.1%) patients were followed up for 12 months postpartum.Conclusions: The authors found that the risk of maternal mortality in the severe PH group was significantly higher than that in the mild-moderate group, highlighting the importance of pulmonary artery pressure screening before pregnancy, early advice on contraception, and multidisciplinary care.